DEVELOPMENT OF LETTUCE (Lactuca sativa) IN HYDROPONICS TREATED WITH LOW FREQUENCY ELECTRIC PULSES - Tellez, Hayver Olaya [UNESP]; Leroy, Karl Auguste [UNESP]; Machado, Letícia Thália Silva [UNESP]; Capuani, Silvia [UNESP]; Jacon, Camila Paula Rossetto Pescatori [UNESP]; Bôas, Roberto Lyra Villas [UNESP] (Brazilian Journal of Irrigation and Drainage - IRRIGA, 2023)
New technologies have increased agricultural production worldwide, and leafy vegetables, such as lettuce, have gained commercial prominence in Brazil because they are the most consumed fresh. Methods such as hydroponics raise productivity thanks to their technification level but can still be improved. There are works and reports that indicate that the application of low-frequency electrical pulses enhances culture productivity, so it is necessary to perform detailed studies. In this sense, the present work aims to evaluate the influence on the development of hydroponic lettuce at a vegetation house using an anti-inconstation electronic system. The entirely randomized design was used in a factorial scheme with 3x2x3 subsubdididids with four repetitions. The factors evaluated were frequency of the use of the electronic system (constant, intermittent and unused), two fertilization levels of 80% and 100% of the recommended solution by Furlani et al. (1999) and three production cycles. The use of constant low-frequency electrical pulses resulted in lower averages for growth variables. A dosage fertilization level of 80% promoted the best results under stress conditions per temperature, and the treatment of intermittent electrical pulsed irrigation water provided results similar to conventional treatment in hydroponic lettuce culture.
DESENVOLVIMENTO DA ALFACE (Lactuca sativa) EM HIDROPÔNIA TRATADA COM PULSOS ELÉTRICOS DE BAIXA FREQUÊNCIA
Keywords: irrigation; nft; production; technology